Comparative analysis of the curriculum and physics textbooks for the 7th grade in Romania, Russia and the Republic of Moldova from the point of view of supporting the concept of lifelong learning competences - CALALB, Mihail; DABIJA, Viorel (Acta et Commentationes, Sciences of Education, 2024)
In this paper, the lifelong learning competencies supported by physics textbooks for the 7th grade from Romania, Russia, and the Republic of Moldova were studied. Additionally, it was investigated whether there is any discrepancy between the competency units declared in the curriculum and the content and structure of the textbooks. A comparative analysis was conducted on Unit 2 “Mechanical Phenomena. Interactionsˮ from the Romanian textbook, Chapter 2 “Interaction of Bodiesˮ from the Russian textbook, and Chapter 2 “Interactionsˮ from the Moldovan textbook. It was found that the Romanian textbook emphasizes the development of technological skills and critical and analytical thinking through the conduct and analysis of experiment results within each lesson, as well as problem-solving skills by examining complex real-world situations. However, the Romanian curriculum lacks specific competency units for the learning unit. The Russian textbook is distinguished by a clear, structured, and concise presentation of the material, and the Russian curriculum includes a short list of cognitive objectives that fully reflect the constructivist nature of learning. It was established that the Moldovan textbook supports autonomous learning, problem-solving, and technological skills, corresponding in such a way to the curriculum.